2017
DOI: 10.1182/blood-2016-09-740787
|View full text |Cite
|
Sign up to set email alerts
|

A phase 1b study of isatuximab plus lenalidomide and dexamethasone for relapsed/refractory multiple myeloma

Abstract: Key Points• Isatuximab (anti-CD38 monoclonal antibody) given with lenalidomide/ dexamethasone is active in heavily pretreated relapsed/ refractory myeloma • Overall, the safety profile of this combination is similar to the characteristic safety profiles of the individual agents. remained on treatment at data cutoff. Isatuximab-lenalidomide-dexamethasone was generally well tolerated with only 1 dose-limiting toxicity reported (grade 3 pneumonia at 20 mg/kg QW/ Q2W); the MTD was not reached. The most common isat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
141
0
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 151 publications
(151 citation statements)
references
References 32 publications
4
141
0
6
Order By: Relevance
“…Overall, the safety profile of this combination was consistent with the safety profile of single-agent ISA and the combination of Len/dex alone [31,38]. Treatment of this heavily pretreated patient population (median five prior lines) with ISA plus Len/dex resulted in an ORR of 56%, including 17 (32.7%) VGPRs and two (3.8%) stringent complete responses (sCRs) [31]. The ORRs among patients refractory to Len, or both an IMiD and a PI were 52% (n = 42) and 45% (n = 38), respectively.…”
supporting
confidence: 60%
See 4 more Smart Citations
“…Overall, the safety profile of this combination was consistent with the safety profile of single-agent ISA and the combination of Len/dex alone [31,38]. Treatment of this heavily pretreated patient population (median five prior lines) with ISA plus Len/dex resulted in an ORR of 56%, including 17 (32.7%) VGPRs and two (3.8%) stringent complete responses (sCRs) [31]. The ORRs among patients refractory to Len, or both an IMiD and a PI were 52% (n = 42) and 45% (n = 38), respectively.…”
supporting
confidence: 60%
“…Therapy options in these patients are limited, and therefore new treatments which improve outcomes and survival are required. ISA has previously demonstrated anti-MM activity in patients who are refractory to currently available IMiDs and/ or PIs, and those with high-risk cytogenetic abnormalities [31,39,46]. At the dose selected for the ICARIA-MM study (10 mg/kg once a week/every 2 weeks), ISA in combination with Pom/dex showed clinical efficacy in a heavily pretreated population [44].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations